Félicienne, Jules, Robert et les autres.... : Les ateliers arts plastiques du - Beeldende kunst in - Art at CRéAHM-Bxl. - Chapelle, Véronique; Bidlot, Jeanine; Cardinal, Roger; Dejace, Anne-Sophie; Dejasse, Erwin; Hoet, Jan; Leemans, Didier; Merland, Bénédicte (Brussel : CRéAHM-Bxl, 2006)
Ahruil, Abderrahmane ; Buyse, Roland ; César, Jules ; Cottone, Massimo ; Denayer, Isabelle ; Detiège, Julien ; Duquenne, Pascal ; González, Manuel ; Gonzalez, Paloma ; Goossens, Roland ( Gos ) ; Ladrière, Patrick ; Meert, Magali ; Moreau, Marie-Jeanne ; Moszkowicz, Richard ; Ndaiziga, Anne ; De Peet, Pierre ; Ricker, Lynette ; Serroukh, Nouzha ; De Smedt, Willy ; Sterckx, Daniel ; Vanhove, Félicienne ; Verschraegen, Jacques ; Vincke, Pascale ; De Zaeytijd, Robert ; Zbierski, Nicole
boek